Implantation of the Subcutaneous Implantable Cardioverter-Defibrillator: An Evaluation of 4 Implantation Techniques. (January 2017) - Brouwer, Tom F.; Miller, Marc A.; Quast, Anne-Floor B.E.; Palaniswamy, Chandrasekar; Dukkipati, Srinivas R.; Reddy, Vivek; Wilde, Arthur A.; Willner, Jonathan M.; Knops, Reinoud E.
Abstract : Background—: Alternative techniques to the traditional 3-incision subcutaneous implantation of the subcutaneous implantable cardioverter-defibrillator may offer procedural and cosmetic advantages. We evaluate 4 different implant techniques of the subcutaneous implantable cardioverter-defibrillator. Methods and Results—: Patients implanted with subcutaneous implantable cardioverter-defibrillators from 2 hospitals between 2009 and 2016 were included. Four implantation techniques were used depending on physician preference and patient characteristics. The 2- and 3-incision techniques both place the pulse generator subcutaneously, but the 2-incision technique omits the superior parasternal incision for lead positioning. Submuscular implantation places the pulse generator underneath the serratus anterior muscle and subfascial implantation underneath the fascial layer on the anterior side of the serratus anterior muscle. Reported outcomes include perioperative parameters, defibrillation testing, and clinical follow-up. A total of 246 patients were included with a median age of 47 years and 37% female. Fifty-four patients were implanted with the 3-incision technique, 118 with the 2-incision technique, 38 with submuscular, and 37 with subfascial. Defibrillation test efficacy and shock lead impedance during testing did not differ among the groups; respectively, P =0.46 and P =0.18. The 2-incision technique resulted in the shortest procedure duration and time-to-hospital discharge compared with the other techniques ( P <0.001). A total of 18 complications occurred, but there were no significant differences between the groups ( P =0.21). All infections occurred in subcutaneous implants (3-incision, n=3; 2-incision, n=4). In the 2-incision group, there were no lead displacements. Conclusions—: The presented implantation techniques are feasible alternatives to the standard 3-incision subcutaneous implantation, and the 2-incision technique resulted in shortest procedure duration. Abstract : Supplemental Digital Content is available in the text.